Persistence in studies in relation to learning approaches and first-year grades: a study of university chemistry students in Finland. Issue 3 (17th June 2019) - Lastusaari, Mika; Laakkonen, Eero; Murtonen, Mari
Abstract : Changing majors or dropping out are of great concern to universities worldwide, but the role of learning approaches in terms of students' persistence has not been previously studied. Changing majors, especially in chemistry, is a severe problem in Finland. Here, learning approach data were collected with the ChemApproach questionnaire from 733 bachelor-level students at four Finnish universities. Students intending to change majors showed stronger submissive surface approaches and weaker active deep approaches than those intending to persist in chemistry. The ChemApproach data were complemented with information on actual persistence and first-year grades from a smaller sample from one university ( N = 177). A practical deep approach in chemistry studies combined with relatively high grades was shown to be connected to persistence, while a desire to change majors combined with high grades resulted in the actual changing of majors. A high submissive surface approach indicated students at risk of dropping out completely.